2004
DOI: 10.1002/ps.850
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide loss following application to a railway

Abstract: Railways have been identified as a potential source of herbicides detected in surface and groundwaters, but there are few data to support this theory. Two studies were undertaken to investigate the fate of herbicides applied to railway trackbeds: a pilot study in a section of a disused, but intact, cutting where runoff and throughflow were sampled from trenches adjacent to the treated area, and a larger scale study on 0.75 km of embankment where surface water from the drainage ditch at the base of the embankme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Due to the coarse texture and low organic matter content of railway embankments, there is much concern that application of herbicides to railways may lead to groundwater contamination. Several studies have investigated the leaching of pesticides from railway tracks and, with some exceptions, most of them indicate that the leaching potential is considerable and that concentrations in the groundwater beneath the track may significantly exceed the EU limit for drinking water of 0.1 µg l -1 if the application rate is too high (Torstensson, 1983;1985;Lode and Meyer, 1999;Schmidt et al, 1999;Börjesson et al, 2004;Ramwell et al, 2004;Torstensson and Börjesson, 2004;Torstensson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the coarse texture and low organic matter content of railway embankments, there is much concern that application of herbicides to railways may lead to groundwater contamination. Several studies have investigated the leaching of pesticides from railway tracks and, with some exceptions, most of them indicate that the leaching potential is considerable and that concentrations in the groundwater beneath the track may significantly exceed the EU limit for drinking water of 0.1 µg l -1 if the application rate is too high (Torstensson, 1983;1985;Lode and Meyer, 1999;Schmidt et al, 1999;Börjesson et al, 2004;Ramwell et al, 2004;Torstensson and Börjesson, 2004;Torstensson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Railway track beds generally have low microbial activity and functional microbial diversity compared with most agricultural soils (Smith et al, 1981;Cederlund et al, 2008), and hence the dissipation of herbicides applied to railway tracks may diff er considerably from that on arable land (Torstensson et al, 2002;Börjesson et al, 2004;Cederlund et al, 2007). Several studies have indicated that herbicide use on railways contributes to surface water and groundwater contamination (Schweinsberg et al, 1999;Ramwell et al, 2004;Skark et al, 2004), and it seems prudent to evaluate the behavior of herbicides intended for railway use thoroughly before approval.…”
Section: Degradation and Leaching Of Fluroxypyr After Application To mentioning
confidence: 99%
“…In many countries, weed control on railway tracks relies on glyphosate [1][2][3]. Glyphosate is a broad-spectrum herbicide with systemic properties [4] and, therefore, shows good activity not only against annual, but also most perennial weeds, including weeds with deep roots that are commonly present on railway tracks.…”
Section: Introductionmentioning
confidence: 99%